2023
DOI: 10.3390/jpm13030553
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and the Role of Adjuvant Chemotherapy in Pathological Node-Negative T3 Gastric Cancer

Abstract: The role of adjuvant chemotherapy in pathological T3N0M0 (pT3N0M0) gastric cancer (GC) remains unclear. The aim of this study was to analyze the prognostic factors of patients with pT3N0M0 GC and to clarify which ones could benefit from adjuvant chemotherapy. A total of 137 patients with pT3N0M0 GC were recruited between 1994 and 2020. Clinicopathological factors and adjuvant chemotherapy regimens were retrospectively collected. Prognostic factors of disease-free survival (DFS) and cancer-specific survival (CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(46 reference statements)
0
3
0
Order By: Relevance
“…I read with great interest the well-written and well-made study by Yi-Fu Chen et al recently published in the “ Journal of Personalized Medicine ” [ 1 ].…”
mentioning
confidence: 99%
“…I read with great interest the well-written and well-made study by Yi-Fu Chen et al recently published in the “ Journal of Personalized Medicine ” [ 1 ].…”
mentioning
confidence: 99%
“…We appreciate the authors very much for their interest in our article “Prognostic factors and the role of adjuvant chemotherapy in pathological node-negative T3 gastric cancer” [ 1 ]. We also greatly agree with their comments that to identify clinical and molecular predictive and prognostic factors in patients at high risk of recurrence who could benefit from the adjuvant chemotherapy is important [ 2 ].…”
mentioning
confidence: 99%
“…We also greatly agree with their comments that to identify clinical and molecular predictive and prognostic factors in patients at high risk of recurrence who could benefit from the adjuvant chemotherapy is important [ 2 ]. The patients enrolled during 1994 and 2020 in our study did not receive neoadjuvant chemotherapy [ 1 ]. In this regard, recent randomized controlled studies recruiting resectable advanced gastric cancer have indicated that neoadjuvant chemotherapy (NAC) downstages the tumor and increases pathological complete response rate, with significantly longer progression-free survival in the NAC group [ 3 , 4 ].…”
mentioning
confidence: 99%